Weniger Tamoxifen als Prophylaxe bei Brustkrebsvorstufen? (Deutsche Zeitschrift für Onkologie, 2020)
Decensi A, Puntoni M, Guerrieri-Gonzaga A et al. Randomized placebo controlled trial of low-dose tamoxifen to prevent local and contralateral recurrence in breast intraepithelial neoplasia. J Clin Oncol 2019; 37: 1629–1637. doi:10.1200/JCO.18.01779